2015
DOI: 10.1503/cjs.013214
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of surgical neuromonitoring data in Canada: a survey of practising surgeons

Abstract: Intraoperative neuromonitoring is a specialized skill set performed in the oper ating room to reduce the risk of neurologic injury. There appears to be a short age of qualified personnel and a lack of Canadian guidelines on the perform ance of the task. We distributed a webbased survey on the attitude of the surgeons to the interpretation of intraoperative neuromonitoring data among surgeons who use the technique. At present, most of the interpretation is per formed by either technologists or by the surgeons t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…A recent British study, which used a modified synoptic reporting system i n v o l v i n g m o r e t h a n 3 6 0 0 0 patients and 297 trainees, found that only 41% of the trainees achieved a colonoscopy completion rate of 90% after 200 colonosco pies. 1 This result is consistent with the recommendation by Cancer Care Ontario of a minimum of 300 cases to achieve competency.…”
supporting
confidence: 88%
“…A recent British study, which used a modified synoptic reporting system i n v o l v i n g m o r e t h a n 3 6 0 0 0 patients and 297 trainees, found that only 41% of the trainees achieved a colonoscopy completion rate of 90% after 200 colonosco pies. 1 This result is consistent with the recommendation by Cancer Care Ontario of a minimum of 300 cases to achieve competency.…”
supporting
confidence: 88%
“…According to the American Medical Association, Policy H-410.957, IONM is the practice of medicine and its interpretation requires a suitably qualified practitioner (Policy H-35.971 and confirmed by the IONM Workgroup of the AMA in 2013). This policy was referenced by Norton et al [1] in the author response to Wilkinson & Kaufmann's letter to the editor [3]. However, because there are no standards of care for IONM in Canada and IONM has not been declared to be the practice of medicine, the vast majority of surgical centers in Canada do not use the services of a qualified clinical neurophysiologist.…”
Section: Medicolegal Responsibility and Accountabilitymentioning
confidence: 99%
“…It is a paradox that given the advanced nature of IONM in the USA compared to IONM in Canada, it is incomprehensible that CANM, without a shred of evidence to support its position, is opposed to applying the established and regulated American service delivery models to Canada. In response to Wilkinson & Haufmann [3], Norton et al [1] It is worthy to note that Canadian patients are becoming more and more informed about surgical outcomes and medical malpractice. For better or for worse, patients are becoming more litigious, as represented by an increased number of lawsuits across Canada, judging surgeons and in extension IONM technologists, accountable for medical malpractice.…”
Section: Medicolegal Responsibility and Accountabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the response rate from the survey is unknown. 4 Without knowing the proportion of the target population represented by the survey data, the results lack statistical rigor. These are classic pitfalls in survey-style research and compromise any major conclusions drawn from this work.…”
mentioning
confidence: 99%